Quantitative Ultrasound Measurement of the Calcaneus in Southeast Asian Children With Thalassemia: Comparison With Dual-Energy X-ray Absorptiometry - Sani, F.M.; Sarji, S.A.; Bilgen, M. (Rockville, 2011)
Objectives- The purpose of this study was to test the hypothesis that quantitative ultrasound properties of the calcaneus in Southeast Asian children treated for thalassemia have different characteristics than those of their healthy counterparts and thereby can be used for assessing the risk of osteoporosis. Methods- Broadband ultrasound attenuation and the speed of sound were measured from groups of thalassemic and healthy children and compared with bone mineral density (BMD) estimated from dual-energy X-ray absorptiometry to determine intergroup and intragroup dependencies of the measurements and variations with differences in sex and anthropometric characteristics. Results- Broadband ultrasound attenuation and speed of sound measurements were found to be independent of sex but dependent on age in the thalassemic children. Consistently, broadband ultrasound attenuation had lower values and the speed of sound had higher values compared with those of the healthy children in each age group. Broadband ultrasound attenuation correlated well with the speed of sound and also with age, weight, and height, but the speed of sound did not show an association with these parameters. Broadband ultrasound attenuation correlated moderately with BMD in the lumbar spine and whole body, but the corresponding association was much weaker for the speed of sound. In the thalassemic children, both broadband ultrasound attenuation and BMD increased with age as they grew older but not fast enough compared with the healthy children, and the risk of osteoporosis was greater at older ages. Conclusions- Calcaneal quantitative ultrasound may be used as a diagnostic screening tool for assessing the bone status in thalassemic Southeast Asian children and for deciding whether further dual-energy X-ray absorptiometry is needed, particularly in those who are at a greater risk for osteoporosis as identified by low body weight and height.